Curcumin, Gut Microbiota, and Neuroprotection - Di Meo, Francesco; Margarucci, Sabrina; Galderisi, Umberto; Crispi, Stefania; Peluso, Gianfranco (Nutrients, 2019)
Curcumin, a nontoxic, naturally occurring polyphenol, has been recently proposed for the management of neurodegenerative and neurological diseases. However, a discrepancy exists between the well-documented pharmacological activities that curcumin seems to possess in vivo and its poor aqueous solubility, bioavailability, and pharmacokinetic profiles that should limit any therapeutic effect. Thus, it is possible that curcumin could exert direct regulative effects primarily in the gastrointestinal tract, where high concentrations of curcumin are present after oral administration. Indeed, a new working hypothesis that could explain the neuroprotective role of curcumin despite its limited availability is that curcumin acts indirectly on the central nervous system by influencing the “microbiota–gut–brain axis”, a complex bidirectional system in which the microbiome and its composition represent a factor which preserves and determines brain “health”. Interestingly, curcumin and its metabolites might provide benefit by restoring dysbiosis of gut microbiome. Conversely, curcumin is subject to bacterial enzymatic modifications, forming pharmacologically more active metabolites than curcumin. These mutual interactions allow to keep proper individual physiologic functions and play a key role in neuroprotection.